When do firms leave cartels? Determinants and the impact on cartel survival - Michael Hellwig; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We use a dataset of 615 firms which participated in 114 illegal cartels - convicted by the European Commission between 1999 and 2016 - to investigate the determinants of the duration of a firm's participation in a cartel. Applying a Weibull proportional hazard model with a particular focus on the impact of internal and external time-varying determinants, we find that firms show an increased probability to leave a cartel if prior exits occurred as well as in periods of high demand growth. However, we find a reduced exit probability in situations of prior entries to the cartel or in periods of high interest rates. Additional estimations on the cartel level further suggest that firm exits increase the probability of a cartel breakdown substantially.
urn:nbn:de:bsz:180-madoc-418869
Keywords: C41; K21; L41; 330; Survival Analysis; Cartels; Duration; European Union